2021
DOI: 10.1017/s1431927621000519
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3D Characterization of Nanoporous Gold Nanoparticles by Transmission Electron Microscopy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…(a) particle I, (b) particle II. Reproduced with permission from ref Copyright 2021 The Author(s) under License CC-BY.…”
Section: Tuning Of Structure and Composition During Dealloyingmentioning
confidence: 99%
See 4 more Smart Citations
“…(a) particle I, (b) particle II. Reproduced with permission from ref Copyright 2021 The Author(s) under License CC-BY.…”
Section: Tuning Of Structure and Composition During Dealloyingmentioning
confidence: 99%
“…A comprehensive reconstruction study of porous Au nanoparticles prepared by dealloying has been reported Figure illustrates a reconstruction of a single representative porous Au-rich particle prepared by electrochemical dealloying.…”
Section: Tuning Of Structure and Composition During Dealloyingmentioning
confidence: 99%
See 3 more Smart Citations